Micronutrient concentration of Okra (Hibiscus esculentus) leaves and fruits as influenced by nitrogen fertilization. - ADUAYI, E. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The influence of nitrogen fertilization on Leaf and fruit micronutrient composition of okra plants, was studied in field trials from 1975 to 1977. Leaf-Fe was higher at the vegetative stage than at the flowering and fruiting stages of growth. Its concentration decreased steadily at the vegetative stage as nitrogen rates increased, but the converse occurred at the flowering and fruiting stages. Similar effects were noticed in leaf-Mn. The highest Mn, Cu and Zn accumulations in the leaves were observed at fruiting. Leaf-Cu was low at all stages of growth relative to other micronutrients. Fruit-Fe and Mn were generally low compared to the leaf concentration, while fruit-Cu and Zn were almost as high as the leaf concentration.